Darkon [videorecording (DVD)] - Neel, Andrew; Meyer, Luke; Lipman, Skip; Wells, Kenyon; McArthur, Daniel (PorchLight Entertainment, 2007)
Follows the real-life adventures of an unusual group of weekend 'warrior knights,' fantasy role-playing gamers whose live action battleground is modern-day Baltimore, Maryland, re-imagined as a make-believe medieval world named Darkon.